QUALITATIVE DIFFERENCES IN THE ANTIGENIC COMPOSITION OF INFLUENZA A VIRUS STRAINS - Friedewald, William F. (The Rockefeller University Press, 1944)
A study of the PR8, Christie, Talmey, W.S., and swine strains of influenza A virus by means of antibody absorption tests revealed the following findings: 1. Serum antibody could be specifically absorbed with allantoic fluid containing influenza virus or, more effectively, with concentrated suspensions of virus obtained from allantoic fluid by high-speed centrifugation or by the red cell adsorption and elution technique. Normal allantoic fluid, or the centrifugalized sediment therefrom, failed to absorb antibodies. Influenza B virus (Lee) caused no detectable absorption of antibody from antisera directed against influenza A virus strains, but it specifically absorbed antibody from Lee antisera. 2. The neutralizing, agglutination-inhibiting, and complement-fixing anti-bodies in ferret antisera were completely absorbed only by the homologous virus strain, even though 2 absorptions were carried out with large amounts of heterologous virus strains. 3. PR8 virus appeared to have the broadest range of specific antigenic components for it completely absorbed the heterologous antibodies in Christie and W.S. antisera and left only those antibodies which reacted with the respective homologous strains. The other virus strains (Christie, Talmey, W.S., swine) were more specific in the absorption of heterologous antibodies and completely removed only those antibodies which reacted with the absorbing virus. 4. The absorption tests revealed a higher degree of specificity and individuality of the virus strains than the various cross reactions previously reported. The strain specificity of PR8 virus was equally manifest in absorption tests with ferret sera and with human sera following vaccination. 5. The amount of homologous antibody remaining in a PR8 ferret serum after absorption with PR8 virus, obtained by the red cell adsorption and elution method, varied inversely as the concentration of virus used for absorption. A given concentration of virus, however, absorbed a greater percentage of neutralizing antibodies than either agglutination-inhibiting or complement-fixing antibodies.